Micromagnetic measurements of ferromagnetic materials: Validation of a 3D numerical model. (June 2019) - d'Aquino, Massimiliano; Minucci, Simone; Petrarca, Carlo; Rubinacci, Guglielmo; Tamburrino, Antonello; Ventre, Salvatore
Abstract: This work if focused on (nondestructive) micromagnetic measurements for ferromagnetic materials in view of Material Characterization (MC). The interest in micromagnetic measurements arises from their correlation to mechanical properties. It is well known that the microstructure of a material affects both mechanical and magnetic properties, therefore it is possible to infer mechanical properties from micromagnetic measurements. This is very convenient because micromagnetic measurements can be carried out in a fast, cheap and nondestructive manner, if compared to mechanical measurements. To date, a lot of experimental work has been carried in the past years but there is still some lack of proper numerical models capable of modelling micromagnetic measurements, especially when considering 3D models. In this paper we present an experimental validation of an ad-hoc 3D numerical model capable of modelling the response in micromagnetic characterization of ferromagnetic materials.